Global Business Norms and Islamic Views of Women's Employment. Issue 2 (April 2014) - Syed, Jawad; Van Buren, Harry J.
ABSTRACT: This article examines the issue of gender equality within Islam in order to develop an ethical framework for businesses operating in Muslim majority countries. We pay attention to the role of women and seemingly inconsistent expectations of Islamic and Western societies with regard to appropriate gender roles. In particular, we contrast a mainstream Western liberal individualist view of freedom and equality—the capability approach, used here as an illustration of mainstream Western liberalism—with an egalitarian Islamic view on gender equality. While the article identifies an opportunity for this particular approach to reform patriarchal interpretations and practices of Islam toward gender egalitarian interpretations and practices, it also contests the notions of adaptation and well-being inherent within the capability approach. We suggest that a dialectical approach to understanding the relationships among religion, culture, and business provides a better guide to responsible business action in Muslim Majority countries than does the capability approach.